2020
DOI: 10.7566/jpsj.89.014701
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Doping Effect on Tc in the Undoped (Ce-Free) Superconductor T′-La1.8Eu0.2CuO4 Studied by the Fluorine Substitution for Oxygen

Abstract: We have succeeded in synthesizing electron-doped polycrystalline bulk samples of T'-La 1.8 Eu 0.2 CuO 4-y F y (y = 0 -0.15) by the fluorination of undoped (Ce-free) T'-La 1.8 Eu 0.2 CuO 4 using NH 4 F. The magnetic susceptibility measurements have revealed that the superconducting transition temperature, T c , increases with increasing y, exhibits the maximum of 23 K at y = 0.025, and decreases. The dome-like dependence of T c on the doped carrier concentration in the T'-type (La,Eu)-based cuprates is explaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This result is different from the phase diagram of La 2−x Sr x CuO 4 (LSCO), where the optimum p is ∼0.16 27 . SC states with higher T c are achieved in the lightly doped region with p 0.09, similar to the SC phase diagram of hole-doped T -type La 1.8−x Eu 0.2 (Sr, Ca) x CuO 4 11,28,29 . Thus, it is important to clarify the electronic state of LESCO in superconducting T -type…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…This result is different from the phase diagram of La 2−x Sr x CuO 4 (LSCO), where the optimum p is ∼0.16 27 . SC states with higher T c are achieved in the lightly doped region with p 0.09, similar to the SC phase diagram of hole-doped T -type La 1.8−x Eu 0.2 (Sr, Ca) x CuO 4 11,28,29 . Thus, it is important to clarify the electronic state of LESCO in superconducting T -type…”
Section: Introductionsupporting
confidence: 68%
“…Since the actual p value of 0.09 is reported for pristine LESCO with x = 0.14 26 , it can be concluded that the FL state is formed in the lower p region, contrary to that in T -type LESCO. The formation of the FL state with lower p can be attributed to the smaller size of the charge-transfer gap (∆ CT ) in the parent T *-type RECuO 11,28,29 . This similarity suggests that the doping evolution of the electronic state in LESCO with five oxygen coordination is comparable to that in La 1.8−x Eu 0.2 (Sr, Ca) x CuO 4 with four coordination, than that in LSCO with six coordination.…”
Section: Relevance To T -And T -Type Cupratesmentioning
confidence: 99%
“…To investigate the phase diagram of HTSCs with the Nd 2 CuO 4 -type structure (so-called T'structure), T'-La 1.8 Eu 0.2 CuO 4 (T'-LECO) is one of the most appropriate materials [4,5,6,7,8]. This compound can be both electron-doped by F with O, and hole-doped by Ca or Sr with La, respectively.…”
Section: Introductionmentioning
confidence: 99%